2022
DOI: 10.3390/foods11121700
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Meat and Carcass Quality from Worldwide Native Chicken Breeds

Abstract: The present research aimed to determine the differential clustering patterns of carcass and meat quality traits in local chicken breeds from around the world and to develop a method to productively characterize minority bird populations. For this, a comprehensive meta-analysis of 91 research documents that dealt with the study of chicken local breeds through the last 20 years was performed. Thirty-nine traits were sorted into the following clusters: weight-related traits, histological properties, pH, color tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 141 publications
1
21
0
Order By: Relevance
“…As suggested in González Ariza et al [ 140 ], redundant variables need to be discarded prior to statistical analyses, leading to CHAID decision tree building before the splitting and pruning stages. In line with this premise, on the one hand, L* meat 72 h post-mortem, a* meat 72 h post-mortem, b* meat 72 h post-mortem, and pH 72 h post-mortem were deemed redundant variables and were discarded from further analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As suggested in González Ariza et al [ 140 ], redundant variables need to be discarded prior to statistical analyses, leading to CHAID decision tree building before the splitting and pruning stages. In line with this premise, on the one hand, L* meat 72 h post-mortem, a* meat 72 h post-mortem, b* meat 72 h post-mortem, and pH 72 h post-mortem were deemed redundant variables and were discarded from further analyses.…”
Section: Discussionmentioning
confidence: 99%
“…This variable closely relates to the initial carcass/piece weight of individuals. A loss in carcass weight is produced by the action of the cold air in forced circulation when carcasses are conserved into cooling chambers [ 140 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, strict adherence to the PRISMA guidelines failed to detect any alterations in the journal’s level of recommendation and endorsement ( 41 ) and exhibited restricted suitability in the context of reviews concerning conservation and environmental management. Instead, the methodology selected in the present study was that described by McLean and Navas Gonzalez ( 42 ), which has been reported as an efficient methodology in previous studies ( 18 , 39 , 43 ).…”
Section: Methodsmentioning
confidence: 99%
“…With the improvement in living standards, consumers are looking for higher meat quality and flavor. Local breeds of chickens are gradually occupying the dominant position in the world chicken market and becoming the mainstream of poultry production [ 1 , 2 ]. In addition, research has shown that poultry gelatin can be used as a sustainable alternative to mammalian gelatin [ 3 ].…”
Section: Introductionmentioning
confidence: 99%